Enhanced autophagy in Becn1F121A/F121A knockin mice counteracts aging-related neural stem cell exhaustion and dysfunction. Issue 2 (1st February 2022) - Wang, Chenran; Haas, Michael; Yeo, Syn Kok; Sebti, Salwa; Fernández, Álvaro F; Zou, Zhongju; Levine, Beth; Guan, Jun-Lin
ABSTRACT: Macroautophagy/autophagy is emerging as a major pathway that regulates both aging and stem cell function. Previous studies have demonstrated a positive correlation of autophagy with longevity; however, these studies did not directly address the consequence of altered autophagy in stem cells during aging. In this study, we used Becn1 F121A/F121A knockin mice (designated as Becn1 KI mice) with the F121A allele in the autophagy gene Becn1 to investigate the consequences of enhanced autophagy in postnatal neural stem cells (NSCs) during aging. We found that increased autophagy protected NSCs from exhaustion and promoted neurogenesis in old (≥18-months-old) mice compared with age-matched wild-type (WT) mice, although it did not affect NSCs in young (3-months-old) mice. After pharmacologically-induced elimination of proliferative cells in the subventricular zone (SVZ), there was enhanced re-activation of quiescent NSCs in old Becn 1 KI mice as compared to those in WT mice, with more efficient exit from quiescent status to generate proliferative cells and neuroblasts. Moreover, there was also improved maintenance and increased neuronal differentiation of NSCs isolated from the SVZ of old Becn1 KI mice in in vitro assays. Lastly, the increased neurogenesis in Becn1 KI mice was associated with better olfactory function in aged animals. Together, our results suggest a protective role of increased autophagy in aging NSCs, which may help the development of novel strategies to treat age-related neurodegeneration. Abbreviations: ATG: autophagy related; Baf A1 : bafilomycin A1 ; Becn1 : beclin 1; BrdU: bromodeoxyuridine/5-bromo-2ʹ-deoxyuridine; DCX: doublecortin; GFAP: glial fibrillary acidic protein; GFP: green fluorescent protein; H&E: hematoxylin and eosin; HSCs: hematopoietic stem cells; KI: knockin; MAP1LC3B/LC3: microtubule associated protein 1 light chain 3 beta; mo: month; NSCs: neural stem cells; OB: olfactory bulb; RB1CC1: RB1-inducible coiled-coil 1; ROS: reactive oxygen species; SOX2: SRY (sex determining region Y)-box 2; SGZ: subgranular zone; SVZ: subventricular zone; TMZ: temozolomide; WT: wild type.